2019
DOI: 10.1016/j.jcmgh.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genome-Scale DNA Methylation Analysis of a Large and Unselected Cohort Reveals 5 Distinct Subtypes of Colorectal Adenocarcinomas

Abstract: Background & Aims Colorectal cancer is an epigenetically heterogeneous disease, however, the extent and spectrum of the CpG island methylator phenotype (CIMP) is not clear. Methods Genome-scale methylation and transcript expression were measured by DNA Methylation and RNA expression microarray in 216 unselected colorectal cancers, and findings were validated using The Cancer Genome Atlas 450K and RNA sequencing data. Mutations in epigenetic regulators were assessed usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 60 publications
3
54
1
Order By: Relevance
“…This fits with the aggressive phenotype of these cancers. An alternative hypothesis, supported an age at diagnosis that is similar to conventional pathway cancers 18 and the morphology of our murine adenomas, is that polyps are initiated by APC, acquire a BRAF mutation. If this is the case such lesions must progress extremely rapidly to cancer as they are very rarely identified in large series of conventional adenomas.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This fits with the aggressive phenotype of these cancers. An alternative hypothesis, supported an age at diagnosis that is similar to conventional pathway cancers 18 and the morphology of our murine adenomas, is that polyps are initiated by APC, acquire a BRAF mutation. If this is the case such lesions must progress extremely rapidly to cancer as they are very rarely identified in large series of conventional adenomas.…”
Section: Discussionmentioning
confidence: 60%
“…DNA was isolated from whole blood using the salt precipitation method as previously reported 17 . Cancer samples were snap-frozen in liquid nitrogen and DNA extracted using the AllPrep DNA/RNA/Protein mini kit (QIAGEN, Germany) as previously reported 18 . Exome-sequencing libraries were generated using the Agilent SureSelect Human All Exon V4+UTR capture platform (Agilent, CA, USA).…”
Section: Dna Extraction Library Preparation and Exome Sequencing Of mentioning
confidence: 99%
“…4 Epithelial-mesenchymal transition (EMT) has been considered as a key metastatic step, which is associated with poor prognosis in CRC. 5,6 EMT is a complex process including the dissolution of cell-cell junction and loss of apicobasolateral polarity, which resulted in the formation of migratory mesenchymal cells with invasive properties. 7,8 The decrease of E-cadherin expression and increase of VIM is generally accepted as a hallmark of the EMT process regulated by various transcriptional factors, such as ZEB1, ZEB2, TWIST, SLUG and SNAIL.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In addition to these EMT transcriptional factors (EMT-TFs), recent evidence showed that microRNAs (miRNAs) are also critical for EMT regulation. 6,8 For instance, miRNAs from the miR-200 family repress EMT by directly targeting and downregulating ZEB1/ZEB1/ SNAIL/SLUG via miR-200-binding sites located within their 3′UTRs, resulting in enhanced E-cadherin expression and inhibition of cancer cell migration and motility. [12][13][14] On the contrary, theses EMT-TFs bind directly to the common promoter regions of the miR-200c family and cause transcriptional repression.…”
Section: Introductionmentioning
confidence: 99%
“…The CRC Subtyping Consortium introduced four consensus molecular subtypes (CMS1-4) for CRC, based on gene expression profiles of tumors. Recently, a study by Lochlan et al[53] investigated genome-scale DNA methylation in a large cohort of CRC patients and revealed five distinct CRC subtypes of colorectal adenocarcinomas with different therapeutic biomarkers for CRC treatment. This highlights the need for a better and more inclusive subtype classification approach to enable biomarker discovery and thus inform drug development for CRC.…”
mentioning
confidence: 99%